Determination of Sex from Sternal Bone In Central Delhi Population - Gupta, Mohit; Kumar, Anil; Khanna , SK (Journal of Indian Academy of Forensic Medicine, 2014)
Identification of deceased is an essential part of post-mortem examination. A number of parameters are used for identification however the determination of sex is statistically the most important criteria. It immediately excludes almost half the population, in comparison to age, stature and race which provide wide number of variables. There have been a number of studies regarding sexing of the sternal bone throughout the world but the studies in India especially Delhi, the capital city of India are virtually non-existent. The present study was an attempt to determine the sternal parameters that can be used to identify the sex of an individual, where sternal bone is available. Length of the manubrium was found to be the most reliable criteria of determining sex from sternal bone. Other parameters i.e. Length of mesosternum, Combined length of manubrium and mesosternum, Breadth of first sternebra at its waist, Breadth of third sternebra at its waist, Manubrio corpus index and Relative width index of first and third sternebrae were not found to be useful. The use of multivariate analysis technique was found to increase the probability of determining the sex of individual by sternum.